Answer:
Hope this helps sorry I'm in class right now
Step-by-step explanation:
Using the normal distribution, it is found that the probability is 0.16.
<h3>Normal Probability Distribution</h3>
In a normal distribution with mean
and standard deviation
, the z-score of a measure X is given by:
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
- It measures how many standard deviations the measure is from the mean.
- After finding the z-score, we look at the z-score table and find the p-value associated with this z-score, which is the percentile of X.
In this problem, the mean and the standard deviation are given by, respectively,
.
The proportion of students between 45 and 67 inches is the p-value of Z when <u>X = 67 subtracted by the p-value of Z when X = 45</u>, hence:
X = 67:
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
![Z = \frac{67 - 70}{3}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7B67%20-%2070%7D%7B3%7D)
Z = -1
Z = -1 has a p-value of 0.16.
X = 45:
![Z = \frac{X - \mu}{\sigma}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7BX%20-%20%5Cmu%7D%7B%5Csigma%7D)
![Z = \frac{45 - 70}{3}](https://tex.z-dn.net/?f=Z%20%3D%20%5Cfrac%7B45%20-%2070%7D%7B3%7D)
Z = -8.3
Z = -8.3 has a p-value of 0.
0.16 - 0 = 0.16
The probability is 0.16.
More can be learned about the normal distribution at brainly.com/question/24663213
Let the two sides of a right triangle be equal to one, which means that the hypotenuse is √2
Since cosa=adjacent side / hypotenuse
cos45=1/√2
We can rationalize the denominator by multiplying numerator and denominator by √2
√(2)/2
or if you prefer: √(1/2)
Answer:
see explanation
Step-by-step explanation:
consecutive even integers have a difference of 2 between them
for example 2, 4, 6 are 3 consecutive even integers
In general if we let the first integer be k then the next 2 integers are
k + 2 and k + 4
the sum of these equals 4 times the first integer, that is 4k, hence
k + k + 2 + k + 4 = 4k
3k + 6 = 4k ( subtract 3k from both sides )
6 = k
the 3 consecutive integers are
k = 6
k + 2 = 6 + 2 = 8
k + 4 = 6 + 4 = 10
that is 6, 8 and 10
note that sum = 6 + 8 + 10 = 24
and 4 × 6 = 24
confirming the sum of the 3 integers equals 4 times the first integer
Answer:
True
Step-by-step explanation:
Exponential function means a function of a power. In this example, x is the function and 2 is the power.